Canadian curling coaches' use of psychological skills training - Paquette, K. J.; Sullivan, P. (The Sport Psychologist, 2012)
Multiple conceptual frameworks support the link between coaches` attitudes and behaviors, and their effect on a variety of athlete outcomes, such as performance, motivation, and athlete self-perceptions. The present study explored the relationships among coaches` attitudes and behaviors, with respect to psychological skills training (PST), and the beliefs of their athletes. One hundred and fifteen coaches completed PST attitude (SPA-RC-revised) and behavior measures, while 403 athletes completed two perception measures (CCS and SCI). Structural Equation Modeling showed that the proposed relationships were statistically significant, except for the pathway between coaches` attitudes and their behaviors. Results support the disconnect between coaches` attitudes and behaviors previously established in PST research, as well as the theoretical links between coaches` behaviors and athletes` perceptions (i.e., evaluation of their coach and self-confidence).